Flow-induced Vibrations of two Staggered Circular Cylinders at Low Reynolds Number - Ye, Zehua; Sun, Xu; Zhang, Jiazhong (Journal of Vibration Testing and System Dynamics, 2026)
The effect of flow interference on the flow-induced vibrations (FIVs) of two staggered circular cylinders at low Reynolds numbers is investigated using fluid-structure interaction (FSI) simulations. The FIV mechanical model of the two staggered circular cylinders in a laminar flow is proposed and the corresponding non-dimensional governing equations are presented. An FSI solution procedure is subsequently developed by combining the modified characteristic-based split (CBS) finite element method, dual-time stepping method, segment spring analogy technique, generalized-α method and loosely-coupled partitioned method. The stability and accuracy of the procedures are validated using a benchmark FSI problem concerning the FIVs of a single circular cylinder in a laminar flow. Finally, using the numerical method proposed, the FIVs of two staggered circular cylinders at Re = 200, T/D (space ratio) = 5∼7 and α (inclined angle of the line connecting the two cylinders centers) = 0°∼ 90° are computed, and the effects of T/D and α on the vortex structure, fluid load and FIVs are discussed in detail.